2014
DOI: 10.1186/1756-0500-7-680
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient intake and nutritional status of newly diagnosed patients with cancer from the East Coast of Peninsular Malaysia

Abstract: BackgroundCancer therapy in Malaysia primarily focuses on the clinical management of patients with cancer and malnutrition continues to be one of the major causes of death in these patients. There is a dearth of information on the nutrient intake and status of newly diagnosed patients with cancer prior to the initiation of treatment. The present study aims to assess the nutrient intake and status of newly diagnosed patients with cancer from the East Coast of Peninsular Malaysia.MethodsA cross-sectional study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Previous studies have assessed the dietary intake of oncological patients, mainly focusing on energy and macronutrients intake. Specifically, dietary energy intakes of patients with advanced malignant disease have been previously reported (Bauer et al, 2005a;Bauer and Capra, 2005b;Bosaeus et al, 2001;DeWys et al, 1981;Fearon et al, 2003;Menon et al, 2014;Vidal-Casariego et al, 2015) with average energy intakes ranging between 22 and 24 kcal/kg/day, while higher intakes (25!35 kcal/kg BW) seem to be required for weight maintenance (Baracos, 2006). Regarding protein intakes, previous studies reported a protein intake of <1.5 g/kg/day (Hutton et al, 2006;Vidal-Casariego et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have assessed the dietary intake of oncological patients, mainly focusing on energy and macronutrients intake. Specifically, dietary energy intakes of patients with advanced malignant disease have been previously reported (Bauer et al, 2005a;Bauer and Capra, 2005b;Bosaeus et al, 2001;DeWys et al, 1981;Fearon et al, 2003;Menon et al, 2014;Vidal-Casariego et al, 2015) with average energy intakes ranging between 22 and 24 kcal/kg/day, while higher intakes (25!35 kcal/kg BW) seem to be required for weight maintenance (Baracos, 2006). Regarding protein intakes, previous studies reported a protein intake of <1.5 g/kg/day (Hutton et al, 2006;Vidal-Casariego et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…According to the present results, a substantial proportion of patients exhibited suboptimal micronutrient intakes based on the EARs for healthy individuals, even when the analysis was restricted to well-nourished and overweight/obese patients. Although there are limited studies assessing micronutrient intake in oncological patients, their findings also reveal a high prevalence of micronutrient deficiencies (Gomez Valiente da Silva et al, 2014;Menon et al, 2014). Studies comparing micronutrient status between cancer patients and healthy individuals revealed that cancer patients have lower levels of vitamins A, B, C, D, and E, as well as selenium and zinc (Strohle et al, 2010;Whiteside et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of the 18 studies are summarized in Table 2 [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. Studies were published between 2012-2022 from five of 11 countries (45%) listed in Southeast Asia: Malaysia (n = 10, 56%) [32,[37][38][39][40][41]44,[47][48][49], Vietnam (n = 4, 22%) [33,35,36,42], Philippines (n = 2, 11%) [45,46], Singapore [34] and Thailand [43] (both n = 1, 6%). Half of the studies [32,[38][39][40]42,[45][46][47][48] were published in 2020 or later, while the remaining studies were published from 2012-2019 [33][34][35]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Studies were published between 2012-2022 from five of 11 countries (45%) listed in Southeast Asia: Malaysia (n = 10, 56%) [32,[37][38][39][40][41]44,[47][48][49], Vietnam (n = 4, 22%) [33,35,36,42], Philippines (n = 2, 11%) [45,46], Singapore [34] and Thailand [43] (both n = 1, 6%). Half of the studies [32,[38][39][40]42,[45][46][47][48] were published in 2020 or later, while the remaining studies were published from 2012-2019 [33][34][35][36][37]41,43,44,49]. Nine studies used observational study design, with most (n = 7) undertaken as a prospective observational study [35,36,38,41,43,44,46], retrospective [33] or prospective cohort [40].…”
Section: Study Characteristicsmentioning
confidence: 99%